FACTORS AFFECTING EMPLOYEE PERFORMANCE EMPLOYEES AT THE SATPOL PP OF SOUTH BENGKULU DISTRICT - Cecilia Kontesa; Ida Anggraini; Eska Prima Monique Damarsiwi (Journal of Research in Social Science and Humanities, 2024)
This study aims to determine the effect of ability on employee performance at Satpol PP South Bengkulu Regency, to determine the effect of motivation on employee performance at Satpol PP South Regency and to determine the effect of ability and motivation on employee performance at Satpol PP South Bengkulu Regency. The data collection method in this research is using a questionnaire and the analysis method is multiple linear regression. Based on the results of research and discussion, it is found that ability has a significant effect on the performance of Satpol PP employees of South Bengkulu Regency because the significance value is 0.000 0.05 or the t value is 7.249 t table 2.005. Motivation has a significant effect on the performance of Satpol PP employees of South Bengkulu Regency because the significance value is 0.001 0.05 or the t value is 3.469 t table 2.005. Ability and motivation have a significant effect on the performance of Satpol PP employees of South Bengkulu Regency because the significance value is 0.000 0.05 or the value of F count 395.125 F Table 2.78.  The results of multiple linear regression obtained Y = 4.227 + 0.576X1 + 0.302X2+e. The advice given to the South Bengkulu Regency Satpol PP is to continue to strive to always improve the ability of employees because employees who have good abilities in carrying out their duties will certainly have good performance in carrying out their duties. In addition, the South Bengkulu Regency Satpol PP continues to improve / increase motivation to its employees so that employee performance will be even better.